A Near-Real-Time Ficin-Based Inhibitive Enzyme Assay for Biomonitoring Heavy Metals in Waters Near Kuah’s Jetty, Langkawi (Journal of Environmental Bioremediation and Toxicology, 2024)
Near real-time biomonitoring, particularly through enzyme assays, offers exceptional sensitivity to bioavailable pollutants, delivering rapid results that facilitate timely intervention. This method is crucial for reducing pollution in drinking water systems and safeguarding human and animal health. The marriage of biological and instrumental process of monitoring allows only positive samples be sent for instrumental analysis vastly increasing the frequency of monitoring and reducing cost at the same time. This study demonstrates the application of ficin as an inhibitive enzyme assay for biomonitoring, in a near real time setting, specifically targeting heavy metals in environmental samples from waters near Kuah’s Jetty, Langkawi. Using the ficin dye-binding assay, designed to detect mercury silver (Ag+), (Hg2+), and copper (Cu2+) at sub-ppm levels, we validated its ability to identify trace concentrations of these metals in waters. The assay proved to be sensitive, rapid, and cost-effective, with minimal inhibition (
Keywords: Near Real-Time; Biomonitoring; Inhibitive enzyme assay; Ficin; Heavy metals